Konsep Aliran Mu’tazilah (Sejarah Perkembangan, Tokoh & Aliran Akidah) - Putri, Umi Muti’ah; Ciptadi, Ikhwan; Burhanuddin, Burhanuddin; Karim, Pangulu Abdul; Herni, Zulfiana (MUDABBIR Journal Research and Education Studies, 2024)
The Mu'tazilah school is one of the schools of Islamic theology that has a significant influence on the history of Islamic thought. The beginning of the emergence of the Mu'tazilah school is rooted in theological problems regarding the law for perpetrators of major sins. The Mu'tazilah school states that perpetrators of major sins are in the middle between believers and infidels. In its historical development, this school emerged in the city of Basrah and reached its peak during the Abbasid Dynasty. The writing in this journal uses a qualitative content analysis method with a literature study approach. The purpose of this writing is to examine in depth the history of the development of the Mu'tazilah since its inception. This study will also identify the main figures who played a role in the process of forming and developing the ideology of this school as well as an analysis of the school of faith that is adhered to and groups that are in conflict with this school as well as the contribution of the Mu'tazilah to the study of Islamic thought, especially in the fields of kalam and philosophy.